2018
DOI: 10.1016/j.jpba.2017.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Determination of total plasma oxysterols by enzymatic hydrolysis, solid phase extraction and liquid chromatography coupled to mass-spectrometry

Abstract: The potential use of cholesterol esterases was tested to avoid alkaline hydrolysis for cleavage of plasma esterified oxysterols. The enzymatic hydrolysis was optimized by testing two sources of enzyme-Pseudomonas and bovine pancreas, presence of surfactants, incubation time and amount of enzyme. Free forms of 4β-, 7-, 24-, 25- and 27-hydroxycholesterol (HC) as well 7-ketocholesterol (7-KC) were analyzed by liquid chromatography and mass-spectrometry using the deuterated internal standard, 25-HC(d6). Enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Karuna et al found that the accurate quantification of 7α,25-diHC and 7α,27-diHC could be achieved by processing plasma samples through slow precipitation protein with cold ethanol, while a low-temperature environment is required for the stability of extracts [108]. The Folch and Bligh and Dyer extraction is widely used to extract lipids by using a mixture of chloroform and methanol as lipid extractant, while the volatility of this organic mixture is not suitable for a highthroughput preparation and MS measurements [109][110][111][112]. In addition, hexane, isopropanol, and ethyl acetate present more similar polarities to COPs than chloroform and are also commonly used for the extraction of COPs [113][114][115].…”
Section: Cops Extraction In Biological Samplementioning
confidence: 99%
“…Karuna et al found that the accurate quantification of 7α,25-diHC and 7α,27-diHC could be achieved by processing plasma samples through slow precipitation protein with cold ethanol, while a low-temperature environment is required for the stability of extracts [108]. The Folch and Bligh and Dyer extraction is widely used to extract lipids by using a mixture of chloroform and methanol as lipid extractant, while the volatility of this organic mixture is not suitable for a highthroughput preparation and MS measurements [109][110][111][112]. In addition, hexane, isopropanol, and ethyl acetate present more similar polarities to COPs than chloroform and are also commonly used for the extraction of COPs [113][114][115].…”
Section: Cops Extraction In Biological Samplementioning
confidence: 99%
“…While the presence of hydroxy groups affects the hydrophobicity of the oxysterol moiety and may affect the performance of the extraction, the presence of the sulfate and hydroxy groups in oxysterols sulfates also affects the detection methods that can be used to quantify oxysterol sulfates. In terms of mass spectrometric assays, the oxysterols are usually detected in the positive ion detection mode (Dias et al, 2018;Hautajärvi et al, 2018;Helmschrodt et al, 2013;Mendiara et al, 2018;Murakami et al, 2000), whereas the presence of the sulfate group facilitates the detection of oxysterol sulfates in the negative ion mode. Because oxysterols sulfates occur in residual levels in biological samples, detection of oxysterols sulfates is often F I G U R E Overview of cholesterol sulfate and oxysterol sulfate analysis achieved by targeted detection methods such as multiple reaction monitoring (MRM).…”
Section: Analytical Strategies In the Analysis Of Plasma Oxysterol Sulfates: Current Challengesmentioning
confidence: 99%